Analisis Pengaruh Penerapan Model Discovery Learning pada Pembelajaran Tematik Kelas V SD untuk Meningkatkan Hasil Belajar - Paramitha, Azra Nindya; Putri, Desti Fiqoh Aulia; Sa’diyah, Halimatus; Farhan, Farhan; Khoirunisa, Prima; Tamara, Cyntia Eki; Muhtarom, Taufik (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the impact of the discovery learning model in thematic learning for fifth-grade elementary school students. The research employs a qualitative approach using the Systematic Literature Review (SLR) method. Data sources consist of 20 national journal articles published between 2019 and 2024, retrieved through Google Scholar with the assistance of the Publish or Perish application. Data collection techniques involve identifying articles using keywords such as “discovery learning,” “thematic learning,” and “learning outcomes in elementary school,” followed by screening based on inclusion and exclusion criteria. Selected articles focused on the application of discovery learning in grade five thematic instruction and reported measurable learning outcomes. Data analysis was conducted by reviewing, documenting, and synthesizing findings from the selected articles into descriptive narratives and summary tables. The analysis shows that the implementation of discovery learning increases students’ average learning outcomes from 60.2 to 84.5 and improves mastery levels from 38–60% to 80–100%. Moreover, students’ motivation, activeness, and critical and creative thinking skills also improved significantly. Therefore, discovery learning is recommended as an innovative pedagogical approach to enhance learning engagement and academic achievement in elementary thematic education.